From Theory To Practice: Understanding The Role Of Neural Networks And Deep Learning In Advancing Artificial Intelligence And Machine Learning - Muhammad Ali Khan , Aiman Shabbir , Mohd Abdullah Al Mamun , Thai Son Chu , Sahadat Khandakar , Waseema Batool (Migration Letters, 2024)
Objective This study expects to dig into the critical Advancement in neural networks and deep learning that are changing the fields of Artificial intelligence (AI) and Machine learning (ML). Zeroing in on the most recent turns of events, this research evaluates their [1]capability to upgrade prescient precision, work on model execution, and drive development across different applications. The concentrate additionally expects to recognize difficulties and future headings for coordinating these advances in commonsense settings. Methodology A blended technique approach was utilized, joining quantitative investigation with Qualitative contextual investigations. Quantitative information was accumulated from scholarly diaries, industry reports, and artificial intelligence benchmarks, while qualitative experiences were gotten through interviews with artificial intelligence scientists, industry specialists, and professionals. Measurable investigations, including connection and relapse, were led utilizing the Python programming language. Topical investigation was applied to the subjective information to distinguish winning patterns and concerns. Results The Research uncovered critical progressions in convolutional neural networks (CNNs), recurrent neural networks (RNNs), and their reconciliation with support learning for modern Artificial intelligence applications. Key difficulties distinguished included moral contemplations, information security issues, and differences in admittance to state of the art Artificial intelligence advances. Connection examination showed major areas of strength for a connection between the reception of cutting-edge neural network strategies and upgrades in model execution (r = 0.62, p < .01), and a striking negative connection between’s absence of admittance to these advances and venture delays (r = - 0.50, p < .01). Relapse investigation showed that consistent expert turn of events and institutional help are basic indicators of effective execution of cutting-edge artificial intelligence methods (β = .400, t = 6.10, p < .001, R² = .160 for institutional help; β = .370, t = 5.30, p < .001, R² = .140 for proficient turn of events). Conclusion This study gives an exhaustive assessment of late leap forwards in neural networks and deep learning, featuring the significance of vital preparation and moral contemplations in expanding the capability of these progressions. The discoveries recommend that designated mediations and strong emotionally supportive networks can prompt critical upgrades in AI and ML applications. The research highlights the requirement for ceaseless advancement and joint effort to guarantee that new artificial intelligence innovations go about as impetuses for positive results and evenhanded access. These experiences make ready for future research pointed toward enhancing the job of new disclosures and developments in tending to the advancing requirements of AI and ML.